Online Virtual Nursing Placements: A Case Study on Placement Expansion - Amanda J. Wagg PhD, RGN, SCPHN-HV, IBCLC, QN; Kate Morgan BSc, PGdip, RGN SCPHN-SN (SAGE Publishing, 2022)
Introduction A need to increase student placements, in a culture that is under unprecedented demand, means that practice providers and partner higher education institutions need to find new and innovative ways to ensure quality learning experiences for students. Virtual placements are just one way of providing student placements, and this study presents a case for this. Objective This research aims to explore the student's experience of virtual blended placements and to consider future sustainability. Method This is a qualitative, exploratory study observing the attitudes, thoughts, and feelings of student nurse experiences of online virtual nursing placements. Key cases were identified, and two participants were asked to reflect upon their experiences of the blended virtual learning placement. Student evaluations, and virtual placement day plans, form part of the data collection, and results are presented in a theory building and comparative approach, adopting pattern matching. Results Three themes emerged from the narratives, supported by student evaluations and day plans. Students reviewed the placement positively in that they were able to achieve their required practice proficiencies. Second, they discussed the way in which the virtual days were facilitated and that building relationships with professionals and peers while on placement was of high importance. Conclusion This case study presents a novel and unique student experience within a 0-19 community nursing service, which through 3 days of practice placement supported by two virtually taught days, students were able to reach their practice proficiencies. This virtual placement model offers a unique way to reduce the pressures on frontline staff and enriches the students' experiences.